Preeclampsia complicated by advanced maternal age: a registry-based study on primiparous women in Finland 1997-2008 - Lamminpää Reeta; Vehviläinen-Julkunen Katri; Gissler Mika; Heinonen Seppo (BMC, 2012)
Abstract Background Preeclampsia is a frequent syndrome and its cause has been linked to multiple factors, making prevention of the syndrome a continuous challenge. One of the suggested risk factors for preeclampsia is advanced maternal age. In the Western countries, maternal age at first delivery has been steadily increasing, yet few studies have examined women of advanced maternal age with preeclampsia. The purpose of this registry-based study was to compare the obstetric outcomes in primiparous and preeclamptic women younger and older than 35 years. Methods The registry-based study used data from three Finnish health registries: Finnish Medical Birth Register, Finnish Hospital Discharge Register and Register of Congenital Malformations. The sample contained women under 35 years of age (N = 15,437) compared with those 35 and over (N = 2,387) who were diagnosed with preeclampsia and had their first singleton birth in Finland between 1997 and 2008. In multivariate modeling, the main outcome measures were Preterm delivery (before 34 and 37 weeks), low Apgar score (5 min.), small-for-gestational-age, fetal death, asphyxia, Cesarean delivery, induction, blood transfusion and admission to a Neonatal Intensive Care Unit. Results Women of advanced maternal age (AMA) exhibited more preeclampsia (9.4%) than younger women (6.4%). They had more prior terminations (<0.001), were more likely to have a body mass index (BMI) >25 (<0.001), had more in vitro fertilization (IVF) (<0.001) and other fertility treatments (<0.001) and a higher incidence of maternal diabetes (<0.001) and chronic hypertension (<0.001). Multivariate logistic regression indicated that women of AMA had higher rates of: preterm delivery before 37 weeks 19.2% (OR 1.39 CI 1.24 to 1.56) and before 34 weeks 8.7% (OR 1.68 CI 1.43 to 2.00) low Apgar scores at 5 min. 7.1% (OR 1.37 CI 1.00 to 1.88), Small-for-Gestational Age (SGA) 26.5% (OR 1.42 CI 1.28 to 1.57), Asphyxia 12.1% (OR 1.54 CI 1.34 to 1.77), Caesarean delivery 50% (OR 2.02 CI 1.84 to 2.20) and admission to a Neonatal Intensive Care Unit (NICU) 31.6% (OR 1.45 CI 1.32 to 1.60). Conclusions Preeclampsia is more common in women with advanced maternal age. Advanced maternal age is an independent risk factor for adverse outcomes in first-time mothers with preeclampsia.